Penerapan Model PBL Kombinasi Pendekatan TPACK Media Interaktif Meningkatkan Keterampilan Memecahkan Masalah Serta Hasil Belajar - Chabelita Puspita Sari; Radiansyah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Based on the observations, problem solving skills are still low and student learning outcomes are also not optimal. Indeed, the learning model used is not optimal, the approach is not appropriate, and the means of interaction required are not appropriate, thus they have an impact on students' development in understanding the concepts. math. The solution to this problem can be using creative learning by applying the PBL model in combination with the TPACK Media Interactive method. For the purpose of describing teacher’s activities, increasing student activities, analyzing problem-solving skills and student learning outcomes. This research methodology uses Quantitative and qualitative methods with Classroom Action Research (CAR) were conducted in 3 meetings. The subjects of this study are 5th grade students at SDN Mantuil 1 Banjarmasin for the academic year 2022/2023, ie a total of 26 students. The results showed that the teacher’s performance reached 26 points with very good criteria, 96% of the student’s activities scored very positively and 88% of the students' problem-solving ability scored high. The achievement criteria and student achievement is 96% in the completed category. It can be concluded that the teacher’s activities are done well, the student’s academic achievement increase.